MATHEMATICAL MODEL OF A PERSPECTIVE MONETARY ALLOWANCE SYSTEM OF THE MILITARY PERSONNEL OF THE ARMED FORCES OF UKRAINE - Gorodianska, Larysa (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
B a c k g r o u n d . Scientific search for the structure, form, and components of the perspective monetary support system for the servicemen of Ukraine, which should be close to NATO standards is an urgent task. The system’s design should be formed based on a serviceman’s base salary, and legally established additional payments. The base salary should be formed from the amount of payments for military rank and total length of service, the calculation mechanism for which hasn’t been defined clearly. The purpose of this study is to develop a mathematical model of the prospective monetary support system for servicemen, based on their rank and length of service. The object of the study is the system of monetary support for the servicemen of Ukraine and the armies of NATO member countries; the subject of the study is the method of calculating monetary support depending on the military rank and length of service. M e t h o d s . Approximation method was used when processing tabular data on the size support of various categories of NATO servicemen. The method allowed to for calculating the basic salaries of servicemen of Ukraine. The method of analogy was used in the implementation of the features of monetary support servicemen of NATO servicemen for the system of monetary support of Ukraine. The method of mathematical modeling was used in the development of a mathematical model of the monetary support system for the method of nomograms was used for a simplified determination of the base salary size of servicemen, with any length of service and any accrual base. R e s u l t s . Developed mathematical models of basic salaries of servicemen of Ukraine, close to NATO standards. Algorithms for calculating the basic salary of servicemen of all categories, depending on military rank and length of service, and a methodology for their application in the format of simplified nomograms have been formed. C o n c l u s i o n s . A mathematical model of a perspective system of monetary support for the servicemen of Ukraine was formed depending on military rank and length of service, close to NATO standards. This model and algorithms for calculation of the basic salaries of servicemen of all categories are universal, created in relative terms, which makes it possible to vary the base of accrual both for individual categories of servicemen and for groups of categories.